2007
DOI: 10.1172/jci33284
|View full text |Cite
|
Sign up to set email alerts
|

Heterotaxy and complex structural heart defects in a mutant mouse model of primary ciliary dyskinesia

Abstract: Primary ciliary dyskinesia (PCD) is a genetically heterogeneous disorder associated with ciliary defects and situs inversus totalis, the complete mirror image reversal of internal organ situs (positioning). A variable incidence of heterotaxy, or irregular organ situs, also has been reported in PCD patients, but it is not known whether this is elicited by the PCD-causing genetic lesion. We studied a mouse model of PCD with a recessive mutation in Dnahc5, a dynein gene commonly mutated in PCD. Analysis of homozy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
87
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 46 publications
(53 reference statements)
10
87
0
Order By: Relevance
“…Further, the incidence of CHD is significantly increased in heterotaxy patients, when compared with the general population (57% vs. 1% respectively) 129,130 with septal defects and TGA being the most prevalent CHDs. 129 In an ENU mutagenesis screen in mice, 131 a mutation in the gene encoding Dnah5 (a dynein heavy chain) was found to cause situs abnormalities, including heterotaxy (40%) and SI (35%), and many of the mice had associated CHD similar to those observed in the study by Kennedy and colleagues. 129 Together, these studies reflect the importance of nodal cilia and their motility in situs establishment.…”
Section: Nodal Cilia and Heterotaxymentioning
confidence: 64%
“…Further, the incidence of CHD is significantly increased in heterotaxy patients, when compared with the general population (57% vs. 1% respectively) 129,130 with septal defects and TGA being the most prevalent CHDs. 129 In an ENU mutagenesis screen in mice, 131 a mutation in the gene encoding Dnah5 (a dynein heavy chain) was found to cause situs abnormalities, including heterotaxy (40%) and SI (35%), and many of the mice had associated CHD similar to those observed in the study by Kennedy and colleagues. 129 Together, these studies reflect the importance of nodal cilia and their motility in situs establishment.…”
Section: Nodal Cilia and Heterotaxymentioning
confidence: 64%
“…This mouse line has been constantly bred as a homozygous colony for over 50 years, demonstrating that it is robust, viable, and that it demands only normal husbandry, in contrast to the viability issues seen in other models including Dnahc5 [Tan et al, 2007], nm1054 [Lee et al, 2008] and the complex preparatory considerations associated with the Dnaic conditional mutant [Ostrowski et al, 2010]. We have not only confirmed that the iv model has static respiratory cilia at 37 • C, but that it develops PCD-related disease including rhinitis, sinusitis, and otitis media.…”
Section: Discussionmentioning
confidence: 99%
“…A significant proportion, including Dnahc5 (MIM# 603335) [Tan et al, 2007], Poll (MIM# 606343) [Kobayashi et al, 2002], and Dnaic1 (MIM# 604366) [Ostrowski et al, 2010], demonstrate additional defects, particularly hydrocephalus and cardiac anomalies, reducing their viability and raising significant animal welfare issues. The repeated demonstration that mutation of human PCD loci in the mouse results in hydrocephalus has led some to suggest an underlying difference in physiology [Ibanez-Tallon et al, 2002;Ostrowski et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Humans and mammals develop all of these problems (Lander et al, 1998), but other animals such as Xenopus rarely if ever demonstrate isomerisms. Additionally, some phenotypes, such as heterotaxia, are quite detrimental to the health of humans and mammals, as evidenced by perinatal lethality of heterotaxic mutants [for example, (Tan et al, 2007)], while heterotaxic tadpoles appear quite healthy and can live for several months (Morokuma et al, 2008a). These observations suggest that there may be some fundamental differences in how animals with very different embryonic architectures establish LR asymmetry (Speder et al, 2007; Palmer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several genes, including nodal, lefty and pitx2, have well characterized asymmetric expression patterns that have been observed in multiple species; the positive- and negative-feedbacks among members of these signaling pathways are well understood (Burdine and Schier, 2000; Schlueter and Brand, 2007; Duboc and Lepage, 2008). Finally, in the third step, information from asymmetric gene expression is amplified and transmitted to several organ systems, and differential migration, proliferation, tension, and adhesion of cells allows for asymmetric development and position of organs (Yost, 1991; Yost, 1992; Gros et al, 2009; Tabin, 2006). …”
Section: Introductionmentioning
confidence: 99%